Assessment and Treatment of Voltage Sag Based on Electric-Process PIT - Kang, Zhongjian; Yuan, Tianyu; Liu, Jiaxuan (Proceedings - International Conference on Harmonics and Quality of Power, 2024)
Based on the strong correlation between petrochemical enterprises and the typical process parameters, an evaluation method combining traditional voltage tolerance curve with process immunity time based on process parameters was proposed. This method constructs a comprehensive evaluation index of safe operation of chemical plant after voltage sag, including electrical parameters and process parameters such as head and flow in the production process, which can realize sensitive identification of electrical parameter collapse and process index imbalance caused by voltage sag. Then, a circuit model is built according to the electrical parameters of a petrochemical enterprise, such as the circuit and the important sensitive load, and the typical sensitive load voltage sag is evaluated and treated. The results show that taking corresponding treatment measures based on the evaluation method of electric-process immune time curve can effectively enhance the stable operation ability of sensitive load and improve the power quality of petrochemical enterprises.